An Attempt at the Automation of the Routing of Mountain Forest Roads with the Use of GIS Spatial Analyses - Gołąb, Janusz; Pirowski, Tomasz (Geomatics and Environmental Engineering, 2019)
The routing of road corridors in the project of a forest road network in the mountains, along with defining the functions of these roads, is the most important activity in the entire task. It must be preceded by a detailed inventory consisting of many factors characterising the analysed transport area, including economic, technical or environmental factors. This study presents an attempt at the semi-automatic routing of road corridors with the use of GIS technology. The original multi-stage methodology proposed by the present authors is based on raster analyses of the Digital Terrain Model at a resolution of 1 m. The initial stage consists in a preliminary outline of the road network being designed, which is performed by an experienced designer on a contour map. Due to the complicated terrain in mountain areas, the pre-determined road sections are divided into sections for which a generalised direction in the form of a straight line can be indicated. On the basis of the azimuths of these particular direction lines, "œtargeted" terrain inclinations are calculated for each section separately, which help in decisions concerning the location of the planned road sections. The results obtained indicate the key role of the initial concept of the designed road network, as outlined by the expert, and based on the expert´s professional experience. The problem lies in strongly varied terrain, which forces the designer to use short sections of corridors. This, in turn, significantly increases the amount of work. Good effects of road routing automation can be obtained in areas where land relief is complicated. The designed locations of road sections must be finally verified in terms of terrain inclination along the designated lines, which is essential for the possibility of subsequent detailed design, construction and use of road sections.